Light-directed trapping of metastable intermediates in a self-assembly process - Joonsik Seo (Nature Portfolio, 2020)
Knowledge about kinetically favored intermediate states in self-assembly processes can provide information about the self-assembly process but trapping these states without changing the reaction conditions is challenging. Here, the authors report a method for trapping metastable intermediates in self-assembly processes that is based on a photopolymerization strategy.